Diving behaviour of humpback whales feeding on overwintering herring in North-Norwegian fjords - Ochoa Zubiri, Kevin (UiT Norges arktiske universitet, 2017)
Since 2011, large numbers of humpback whales have aggregated to feed on Norwegian spring-spawning herring overwintering from late October to February within the fjords of the Troms county in Northern Norway. Whale aggregations are new in this region and little information on the whales’ behaviour is available. How whales dive and forage and how they adjust to the extreme light regime at this latitude is largely unknown. To study this, high-resolution time-depth recorders were attached by suction cups during three winter seasons (2013-2016). A total of 42 tag deployments collected more than 450 hours of diving behaviour and almost 8500 dives. The whales spent a median of ~21% of the time at the surface and over 70% of dives were shallower than 50 m and shorter than 3 min. The deepest dive was recorded at 266 m and the longest dive lasted 21 min. Large behavioral differences were found among individuals. A foraging index was defined as the standardized residuals of a linear regression involving time spent at the bottom of a dive as a function of maximum depth and duration. No common diel pattern was found in the diving behaviour or in the presumed foraging activity of the whales but it was possible to group individuals into clusters. Approximately 2/3 of the whales were found to perform their deepest dives during the lightest hours of the day, while half of the whales seemed to intensify their foraging activity during the darkest hours of the day. These results are in accordance with herring diel vertical migration described in previous overwintering grounds, where fish was located at depth during the day and closer to the surface during the night. This study contributes to a better understanding of this predator-prey relationship and could help assessing the whales’ impact on the herring stock within the fjords. Thus, these findings may play a part in the ecosystem based management of the herring fishery quota for Northern-Norway.